ANIMATION VIDEO AND BOOK COVERS EFECTIVE TO IMPROVE ATTITUDES ABOUT BALANCED NUTRITION OF ELEMENTARY SCHOOL STUDENTS - Hapsari, Sri (Poltekkes Kemenkes Bengkulu, 2025)
The prevalence of obesity in students aged 5-12 years is quite high which is thought to be related to their knowledge and attitudes about balanced nutrition, which can be improved through education using various media. The study aims to assess the effectiveness of animated videos and book covers to increase elementary school students' knowledge and attitudes about balanced nutrition. True experimental research was conducted on two groups of 27 students each, which were determined randomly. One group was given education with an animated video and one group with a book cover. Knowledge and attitudes were measured by questionnaires using questionnaires, before and after treatment. The difference before and after was tested with paired t-test samples and the difference in effectiveness of the two media was tested with independent ttest..The results showed a difference in pre and post knowledge scores in animated videos (32.83±12.93%) and book covers (22.22±14.20%). The difference in pre and post attitude scores in animated videos (7.77±6.90%) and book covers (4.53±6.82%). All of these differences are significant with p=0.001 and p=0.001 in animated videos and p=0.001 and 0.002 on book covers. The difference in knowledge and attitude improvement between animated videos and book covers was 10.61 (p=0.006) and 3.24 (p=0.089). Both media are effective in increasing knowledge and attitudes about balanced nutrition. Animated videos are more effective at increasing knowledge than book covers, but they are equally effective at improving attitudes.